Does odor and taste identification change during hyperemesis gravidarum? - Mehmet Yasar; Mustafa Sagit; Semih Zeki Uludag; Ibrahim Ozcan (Medicinski glasnik, 2016)
Aim: To investigate a difference in odor and taste identification among pregnant women with hyperemesis gravidarum, those with healthy pregnancy and non-pregnant women. Methods: This prospective, controlled study included 33 pregnant women with hyperemesis gravidarum, 33 healthy pregnant and 26 non-pregnant women. For all participants, rhinological examinations were performed. Odor and taste identification were performed by holding Sniffin Sticks test battery (Burghart, Wedel, Germany) in all participants. Results: There was a statistically significant difference in results of odor identification tests among the groups (p=0.031). Rose odor was selected as the most pleasant odor by the hyperemesis gravidarum group, 32 (96.9%). Orange odor was selected as the most pleasant odor by the healthy pregnant women, 33 (100%) whereas the banana odor was selected as the most pleasant odor by the healthy non-pregnant women, 10 (38.4%). In taste identification tests, there was a significant difference in total taste scores among the groups (p=0.003). Conclusion: It is obvious that there is a need to evaluate odor thresholds and other parameters by detailed studies on odor perception in the context of hyperemesis gravidarum.
Keywords: pregnancy; smell; sense of smell